Effects of different banana crop residue hays on ensiling BRS capiaçu grass on fermentation profile, aerobic stability and nutritional value of silage - Silva, Ariadne Freitas; Monção, Flávio Pinto; Rigueira, João Paulo Sampaio; Rocha Júnior, Vicente Ribeiro; Alencar, Amanda Maria Silva; Carvalho, Cinara da Cunha Siqueira; Albuquerque, Carlos Juliano Brant; Silva, Fredson Vieira e; Miorin, Renan Lucas; Sales, Eleuza Clarete Junqueira de (Semina: Ciências Agrárias, 2021)
The objective of this study was to evaluate the BRS capiaçu grass silage combined with different hays of banana crop residue on fermentation profile, aerobic stability and nutritional value. The treatments consisted of elephant grass cv. BRS capiaçu (Pennisetum purpureum Schum.) ensiled with 37.44% banana peel hay, 36.06% banana pseudostem hay and 37.00% banana leaf hay, on a dry matter (DM) basis and control silage (no additive). The experimental design used was completely randomized, with five treatments and five replicates. Forage was collected when it reached 3.5 meters in height (90 days). Experimental PVC silos of known weight, 50 cm long, 10 cm diameter, were used for silage making. For all treatments, silage aerobic stability breakdown started after 64 hours exposure to air. The BRS capiaçu grass control silage or silage combined with pseudostem hay (mean of 73.15 kg t GM-1) presented effluent losses 40.46% higher than those observed for BRS capiaçu grass silage + banana leaf hay and 69.17% in relation the BRS capiaçu grass silage + banana peel hay. The inclusion of banana crop residue (hay) when ensiling BRS capiaçu grass decreased 13.93% gas losses compared to the control silage (mean of 3.11% DM). Higher values of total digestible nutrients, metabolizable energy and digestible energy content was found in BRS capiaçu grass silage + with banana peel hay. The greater in vitro dry matter digestibility and in vitro neutral detergent fiber digestibility was observed for BRS capiaçu grass silage combined with pseudostem hay. The inclusion of 37.44% banana peel hay improves the fermentation profile and aerobic stability of BRS capiaçu grass silage.